Efektivitas Peran Pustakawan Sebagai Mitra Pemustaka Menemukan Sumber Pustaka untuk Penelitian - Mariatul Qibthiyyah (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
The purpose of this study is to describe the effectiveness of the role of librarians as friends in finding library sources for research. The design is a mixed method with the Triangulation Design procedure: Validating Quantitative Data Model. In this model, researchers will collect quantitative data and qualitative data. The next stage is to carry out further analysis by validating the results of quantitative analysis using qualitative results. The population in the study were all lecturers at Lambung Mangkurat University. The sample to determine the effectiveness of the role of librarians in research, namely 100 lecturers. Data were collected by filling out a questionnaire to answer all problem formulations. Also supported by interviewing lecturers to validate the results of filling out a questionnaire about the role of the librarian as a place to find library sources for research. The results of this study is that 54.49% of researchers agree that librarians are effective as friends in finding sources of literature for research. 33.91% of researchers strongly agree. While a small proportion of researchers, namely 0.87% and 0.58%, respectively, stated that they disagreed and disagreed with the statement. The conclusion of this research was the librarian's role has been effective as a friend in finding library resources for research